Value of Periprocedural Electrophysiology Testing During Transcatheter Aortic Valve Replacement for Risk Stratification of Patients With New‐Onset Left Bundle‐Branch Block - Patrick Badertscher; Sven Knecht; Florian Spies; Chloé Auberson; Marc Salis; Raban V. Jeger; Gregor Fahrni; Christoph Kaiser; Beat Schaer; Stefan Osswald; Christian Sticherling; Michael Kühne (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background Despite being the most frequent complication following transcatheter aortic valve replacement (TAVR), optimal management of left bundle‐branch block (LBBB) remains unknown. Electrophysiology study has been proposed for risk stratification. However, the optimal timing of electrophysiology study remains unknown. We aimed to investigate the temporal dynamics of atrioventricular conduction in patients with new‐onset LBBB after TAVR by performing serial electrophysiology study and to deduce a treatment strategy. Methods and Results We assessed consecutive patients undergoing TAVR via His‐ventricular interval measurement prevalve and postvalve deployment and the day after TAVR. Infranodal conduction delay was defined as a His‐ventricular interval >55 milliseconds. Among 107 patients undergoing TAVR, 53 patients (50%) experienced new‐onset LBBB postvalve deployment and infranodal conduction delay was noted in 24 of 53 patients intraprocedurally (45%). LBBB resolved the day after TAVR in 35 patients (66%). In patients with new‐onset LBBB postvalve deployment and no infrahisian conduction delay intraprocedurally, the His‐ventricular interval did not prolong in any patient to >55 milliseconds the following day. Overall, 4 patients (7.5%) with new‐onset LBBB after TAVR were found to have persistent infrahisian conduction delay 24 hours after TAVR. During 30‐day follow‐up, 1 patient (1.1%) with new LBBB and a normal His‐ventricular interval after TAVR developed new high‐grade atrioventricular block. Conclusions Among patients with new‐onset LBBB postvalve deployment, infrahisian conduction delay can safely be excluded intraprocedurally, suggesting that early intracardiac intraprocedural conduction studies may be of value in these patients.